Fuzzy Bounded and Continuous Linear Operators on Standard Fuzzy Normed Spacesa - Jehad R. Kider; Rami M. Jameel (Engineering and Technology Journal, 2015)
In this paper we introduce the definition of standard fuzzy normed space, then we discuss several properties after we give an example to illustrate this notion. Then we define F-bounded operator as an introduction to define a standard fuzzy norm of an operator and if T is a linear operator from standard fuzzy normed space X into a standard fuzzy normed space Y we prove that T is continuous if and only if T is F-bounded.